An eroticized culture? : a critical inquiry into the relationship between Utopia and the erotic in the writings of Sigmund Freud, Wilhelm Reich and Herbert Marcuse - Gerber, Gerhard Anton (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1996.